HEMOLYTIC DISEASE OF THE NEWBORN - Makevic Djuric, Mirjana; Djuric, Milivoje (HEALTH CARE, 2022)
Introduction/Aim: Haemolytic disease of the newborn is haemolytic anaemia that occurs as a consequence of mismatched blood of the parents, that is, the mismatch of blood elements between the mother and fetus in the ABO or Rh system. The aim of this study is to report a case of haemolytic disease of the newborn which occurred as a result of ABO incompatibility. Case report: Indirect hyperbilirubinemia was registered in a female newborn in the 18th hour of life. The blood group of the newborn was A Rh (D) positive, the direct Coombs test was positive and anti-A antibodies were detected in baby’s blood. This case was successfully managed with phototherapy and simple red blood cells transfusion without the need for exchange transfusion. Conclusion: ABO incompatibility can be a major problem in the prenatal, perinatal or neonatal periods. Special attention should be paid to pregnant women whose children from previous pregnancies had hyperbilirubinemia or whose pregnancies were ended in miscarriage.